2017
DOI: 10.3126/ajms.v8i3.16188
|View full text |Cite
|
Sign up to set email alerts
|

Synoviology: a new chapter entitled to joints care

Abstract: A B S T R A C T REVIEW ARTICLE ASIAN JOURNAL OF MEDICAL SCIENCESIn order to extensively investigate on the synovial membrane -related diseases, we outlined a specific medical branch named "Synoviology", targeted to the physiopathology and therapy of synovial membrane dysfunction. We searched Pubmed/Medline using the terms "synovial disease", "therapy", "synovial membrane", "joints" and "drugs", alone and combined. Selected papers from 1960 to 2015 were chosen based on their content (evidence-based quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Proteoglycans comprise proteins covalently bonded to GAGs and play essential roles in regulating cell growth . Palmieri et al elucidated that SF contains proteoglycans and other bioactive molecules, which makes it comparable to snail mucus in terms of complexity. Polyphenols have been previously detected in snail mucus and may be responsible for the antioxidant and anti-inflammatory properties of the material, as reported so far. , The total phenolic content in Cru and SMu were calculated from the calibration curve (Figure S3) to be 116 and 66 μg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteoglycans comprise proteins covalently bonded to GAGs and play essential roles in regulating cell growth . Palmieri et al elucidated that SF contains proteoglycans and other bioactive molecules, which makes it comparable to snail mucus in terms of complexity. Polyphenols have been previously detected in snail mucus and may be responsible for the antioxidant and anti-inflammatory properties of the material, as reported so far. , The total phenolic content in Cru and SMu were calculated from the calibration curve (Figure S3) to be 116 and 66 μg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Articular cartilage in its native state is bathed with a clear and viscous fluid called synovial fluid (SF) . SF serves as the primary source of nutrients to the cartilage tissue and as a lubricant and shock absorber to the joint. , Palmieri et al reported that SF contains proteins, proteoglycans, minerals, sugar, and other bioactive molecules . Whereas some of these constituents of SF are similar in composition and function to the constituents of snail mucus, the snail mucus has been reported to be a complex substance that contains 90–97% water by weight, and the remaining contains a mixture of glycosaminoglycan (GAGs), proteoglycans, hyaluronic acid, glycoproteins, enzymes, metal ions, copper peptides, and antimicrobial peptides. …”
Section: Introductionmentioning
confidence: 99%
“…Aptamer specificity tests were conducted with the two aptamers in the presence of the most two abundant human SF proteins: human serum albumin (HSA; cat. #A3782-1G, St. Louis, MO, USA; 1 mg/mL) and human immunoglobulin G (IgG, I4506; 1 mg/mL, Sigma-Aldrich, USA). , To simulate the situation in real samples (i.e., SF), we selected 12,000 mg/L HSA and 4000 mg/L IgG as our non-target proteins . The concentrations of these proteins were selected according to their concentrations in the real SF.…”
Section: Methodsmentioning
confidence: 99%
“…47,48 To simulate the situation in real samples (i.e., SF), we selected 12,000 mg/ L HSA and 4000 mg/L IgG as our non-target proteins. 48 The concentrations of these proteins were selected according to their concentrations in the real SF.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Rozdíly koncentrací KH mezi jednotlivými skupinami nebyly statisticky významné. Koncentrace KH v synoviální tekutině se nelišily od publikovaných referenčních hodnot 1500-3200 mg/l (8). Koncentrace KH nezávisí na věku, pohlaví, stupni artrózy, ani na závažnosti onemocnění charakterizovaném nutností provedení totální endoprotézy.…”
Section: Výsledkyunclassified